Factors Influencing Soil Nitrification Process and the Effect on Environment and Health - Ayiti, Oluwatobi Esther; Babalola, Olubukola Oluranti (Frontiers in Sustainable Food Systems, 2022)
To meet the global demand for food, several factors have been deployed by agriculturists to supply plants with nitrogen. These factors have been observed to influence the soil nitrification process. Understanding the aftermath effect on the environment and health would provoke efficient management. We review literature on these factors, their aftermath effect on the environment and suggest strategies for better management. Synthetic fertilizers and chemical nitrification inhibitors are the most emphasized factors that influence the nitrification process. The process ceases when pH is <5.0. The range of temperature suitable for the proliferation of ammonia oxidizing archaea is within 30 to 37oC while that of ammonia oxidizing bacteria is within 16 to 23oC. Some of the influencing factors excessively speed up the rate of the nitrification process. This leads to excess production of nitrate, accumulation of nitrite as a result of decoupling between nitritation process and nitratation process. The inhibition mechanism of chemical nitrification inhibitors either causes a reduction in the nitrifying micro-organisms or impedes the amoA gene's function. The effects on the environment are soil acidification, global warming, and eutrophication. Some of the health effects attributed to the influence are methemoglobinemia, neurotoxicity, phytotoxicity and cancer. Biomagnification of the chemicals along the food chain is also a major concern. The use of well-researched and scientifically formulated organic fertilizers consisting of microbial inoculum, well-treated organic manure and good soil conditioner are eco-friendly. They are encouraged to be used to efficiently manage the process. Urban agriculture could promote food production, but environmental sustainability should be ensured.